Genetic susceptibility to cutaneous melanoma in southern Switzerland: role of CDKN2A, MC1R and MITF. (1st November 2016) - Mangas, C.; Potrony, M.; Mainetti, C.; Bianchi, E.; Carrozza Merlani, P.; Mancarella Eberhardt, A.; Maspoli‐Postizzi, E.; Marazza, G.; Marcollo‐Pini, A.; Pelloni, F.; Sessa, C.; Simona, B.; et al.
Summary: Background: Nearly 10% of all cases of cutaneous melanoma (CM) occur in patients with a personal or family history of the disease. Objectives: To obtain information about genetic predisposition to CM in Ticino, the southern region of Switzerland, a zone with moderate‐to‐high CM incidence. Methods: We identified germline mutations in highly CM‐associated genes ( CDKN2A and CDK4 ) and low/medium‐penetrance variants ( MC1R and MITF ) in patients with multiple primary CMs or individuals with one or more CM and a positive family history for CM or pancreatic cancer among first‐ or second‐degree relatives. Healthy blood donors ( n = 146) were included as a control group. Results: From July 2010 to July 2012, 57 patients (41 pedigrees) were included. Twenty‐six were melanoma‐prone families (with at least two cases) and 15 had multiple CMs. Pancreatic cancer was found in six families. The CDKN2A mutation p.V126D was identified in seven patients (four families) with a founder effect, whereas CDKN2A A148T was detected in seven cases (five families) and seven healthy donors (odds ratio 2·76, 95% confidence interval 0·83–9·20). At least one MC1R melanoma‐associated polymorphism was detected in 32 patients (78%) and 97 healthy donors (66%), with more than one polymorphism in 12 patients (29%) and 25 healthy donors (17%). The MITF variant p.E318K was identified in four patients from three additional pedigrees (7%) and one healthy control (0·7%). Conclusions: Inclusion criteria for the Ticino population for genetic assessment should follow the rule of two (two affected individuals in a family or a patient with multiple CMs), as we detected a CDKN2A mutation in almost 10% of our pedigrees (four of 41), MITF p.E318K in 7% (three of 41) and a higher number of MC1R variants than in the control population.